Screening for cardiovascular risk in the masters athlete - Morrison, B. (New Studies in Athletics, 2015)
Regular physical activity is associated with health benefits and "successful aging" in Masters athletes (>35 years-old). Paradoxically, exercise can increase the risk of heart attacks, irregular heart rhythms, and sudden cardiac death (SCD) in those with underlying disease. SDC is, of course, a concern for both individuals and the organisers of sports events, particularly those involving Masters athletes. There are currently a number of strategies to reduce exercise-related SCD, including preparticipation screening prior to vigorous activity. In addition to detecting disease, screening creates an awareness of risk factors associated with the development of cardiovascular disease and educates on the nature and significance of warning signs. To date, however, optimal screening methods have not been universally agreed. This article starts with overviews of cardiovascular risk and the effects of aging on cardiovascular function and then examines various screening protocols in detail, including physical activity and fitness assessments, electrocardiogram, exercise treadmill test, and imaging techniques. It concludes with a summary of 12 key points and recommendations.